1997
DOI: 10.1097/00006982-199705000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Macular Hole Surgery Without Face-Down Positioning

Abstract: This pilot study suggests that successful macular hole closure is possible without face-down positioning. This technique may be an alternative for patients with macular holes in pseudophakic eyes who are unable to assume face-down posturing. Combining cataract surgery with this technique for macular hole repair is reasonable for phakic patients who cannot maintain prone positioning. Major disadvantages of combined surgery include the morbidity of the second procedure and removal of a visually insignificant cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(63 citation statements)
references
References 0 publications
2
61
0
Order By: Relevance
“…Several mechanisms of action of the gas bubble have been postulated, from exertion of a large floatation force on the macula to preventing exposure of the macular hole to vitreous fluid. 4,16,17 The former requires strict prone posturing for effect; however, the latter does not.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of action of the gas bubble have been postulated, from exertion of a large floatation force on the macula to preventing exposure of the macular hole to vitreous fluid. 4,16,17 The former requires strict prone posturing for effect; however, the latter does not.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5 On the other hand greatest perioperative morbidity associated with macular hole surgery is also believed to be due to strict posturing. 6 Attempts at no posturing surgery 7 or use of silicone oil tamponade [8][9][10] have lower success rate and/or additional risks. The role of posturing in macular hole surgery remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…6 In view of this some surgeons have adopted a no posturing regime and one such study reported a 79% surgical success rate though all the phakic eyes underwent simultaneous cataract extraction with intraocular lens implantation. 7 Others have attempted to use silicone oil injection instead of gas to avoid strict posturing [8][9][10] but the technique has added risk of complications related to silicone oil and also requires second surgery for removal of oil. The role of posturing in macular hole surgery remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Fortyeight per cent of eyes attained visual acuity of 20/50. 40 In another series that included 20 eyes, combined surgery with tamponade by 20% C2F6 without face-down posturing resulted in anatomical closure in 90% and improvement in visual acuity by at least 0.3 logMAR units in 95%. 41 An alternative proposal for patients who are unable to perform prolonged face-down posturing is the use of silicone oil tamponade.…”
Section: Surgical Approaches For Macular Holesmentioning
confidence: 96%